FEATURES OF THE ORGANIZATION AND CONDUCT OF EDUCATIONAL PRACTICE OF FUTURE PRIMARY SCHOOL TEACHERS - Yusupov M.M; Tolipov R. M (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is about the peculiarities of the organization and conduct of educational practice, which is an integral part of the higher education program, and the first, second, and third courses of The Bachelor’s degree in primary education are considered educational practice.